Integrating BIM and Feng shui for the assessment of user experience - Zhang, Yining (2019)
As human needs evolve, information technologies and natural environments require a wider perspective of sustainable development, especially when examining the built environment that impacts the central of social-ecological systems. The use of fengshui views and environmental psychology can provide a reliable basis for all decision-making in the design, construction and maintenance cycle, optimize engineering design, reduce the possibility of error loss and rework caused by in human design or violation of ergonomics during the construction phase, in violation of physical knowledge. It also con siders the integration between BIM and human psychology to improve the practical application of BIM in human life. The primary purpose of this study paper was to establish a conception which Chinese traditional Fengshui could be used in BIM and design a digital Fengshui model in BIM software and achieve rational distribution in AEC projects.